Evaluasi Instalasi Pengolahan Air Limbah (IPAL) Domestik dengan Perhitungan Beban Pencemar di Industri Manufaktur PT. X - Miesta, Audy Eka; Amalia, Aussie (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The increase in domestic activities within industrial operations can lead to higher wastewater generation, which may degrade aquatic environmental quality if not managed properly. Evaluating the performance of domestic Wastewater Treatment Plants (WWTPs) is therefore essential to ensure treatment effectiveness and compliance with applicable effluent standards. This study aims to assess the performance of a domestic WWTP based on effluent quality and pollutant load calculations. The research employed a descriptive quantitative approach, with wastewater samples collected at the WWTP outlet using the grab sampling method. The analyzed parameters included pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), oil and grease, ammonia, total coliform, and temperature. The results indicate that all effluent parameters met the domestic wastewater quality standards stipulated in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 68 of 2016.